Cast me out if you will : stories and memoir - Laḷitāmbika Antarjjanaṃ (Stree, 1998)
The stories and the autobiographical fragments in this collection are engaged and critical accounts of life in namboodri households. Set in the 30s-50s, these texts bring alive the world in which Lalithambika Antherjanam (1909-1985) was born. They record in vivid detail the physical incarceration, the mental agony and the terrorizing disciplinary holds of rituals of purity with an intimacy that can only come from one who writes from experience.